Irish pig farmer’s perceptions and experiences of tail and ear biting - Haigh, Amy (Porcine Health Manag, 2019)
Abnormal behaviours such as ear and tail biting of pigs is of significant welfare and economic concern. Currently, pig welfare legislation is under renewed focus by the EU commission and is likely to be enforced more thoroughly. The legislation prohibits routine tail docking and requires adequate enrichment to be provided. In Ireland, tail-docking is still the most utilised control mechanism to combat tail biting, but biting is still widespread even in tail-docked pigs. In addition, as pig farms are almost all fully slatted, bedding type material cannot be provided. Thus, the opinions, and practices of farmers in countries like Ireland, which may need to make significant adaptations to typical pig management systems soon, need to be considered and addressed. We carried out a survey of pig farmers during 2015 in order to gain a greater understanding of the extent of biting on Irish farms, perception on the most important preventive measures, current enrichment use and actions following outbreaks. Fifty-eight farmers from 21 Counties responded with an average herd size of 710 ± 597 sows (range 90–3000 sows). Only two farms had experienced no biting in the last year. Of the farms that had experienced tail biting (88%), 86% had also experienced ear biting. The most common concerns relating to biting were condemnation and reduced productivity of bitten pigs with both receiving an average score of 4 (most serious). Ear biting occurred most commonly in the 2nd stage (approximately 47–81 days from weaning) weaner and tail biting in the finishing stage. The most important preventive measures were felt to be taking care of animal health, restricting density, maintaining an even quality of feed/content and maintaining good air movement. Sixty-five percent of respondents added additional enrichment following an outbreak. Chains were the most common form of enrichment currently used (83%). Those not using chains favoured wood, toys and rope (17%). Identification of the most effective and accessible control and prevention measures both for the animals and for the farming community is thus essential. Improved understanding of the concerns and practices of producers, which this survey contributes to, is a first step towards this aim.